Kinematic Analysis of Gait in the Second and Third Trimesters of Pregnancy. (31st January 2013) - Branco, Marco; Santos-Rocha, Rita; Aguiar, Liliana; Vieira, Filomena; Veloso, António
Abstract : The kinematic analysis of gait during pregnancy provides more information about the anatomical changes and contributes to exercise and rehabilitation prescription. The purposes were to quantify the lower limb kinematics of gait and to compare it between the second and third trimesters of pregnancy and with a control group. A three-dimensional analysis was performed in twenty-two pregnant women and twelve nonpregnant. Repeated Measures and Manova tests were performed for comparisons between trimesters and between pregnant and controls. The walking speed, stride width, right-/left-step time, cycle time and time of support, and flight phases remain unchanged between trimesters and between pregnant and controls. Stride and right-/left-step lengths decreased between trimesters. Double limb support time increased between trimesters, and it increased when compared with controls. Joint kinematics showed a significant decrease of right-hip extension and adduction during stance phase between trimesters and when compared with controls. Also, an increase in left-knee flexion and a decrease in right-ankle plantarflexion were found between trimesters. The results suggested that pregnant women need to maintain greater stability of body and to become more efficient in locomotion. Further data from the beginning of pregnancy anthropometric data may contribute to the analysis.